The Significance and Impact of Screening Preservation Fluid Cultures in Renal Transplant Recipients. (March 2021) - Reticker, Anesia; Lichvar, Alicia; Walsh, Meghan; Gross, Alan E.; Patel, Shree
Introduction: Infectious complications can be a major cause of morbidity and mortality in solid organ transplant recipients. Preservation fluid is necessary to maintain organ viability but may serve as a vector or infection. The utility of screening preservation fluid routinely for microbial growth and the impact of culture-positive preservation fluid is controversial. Research Question: What is the clinical impact of a culture positive preservation fluid in a kidney transplant recipient? Design: This retrospective study was performed to define the incidence of post-operative infection related to PF and examine the negative sequelae of culture-positive PF. One hundred and fifty-two deceased donor renal transplant recipients from January 2015 to December 2017 were included for analysis. Results: Overall, 67% of patients (102/152) received an allograft from a culture-positive PF. Nearly 80% of microbial growth was consistent with skin flora, and coagulase-negative staphylococci was the most frequently isolated organism (56%). Sixty-seven percent of patients (68/102) with culture-positive PF received antimicrobial treatment for an average duration of 5 days. There was no difference in the incidence of infection between patients with culture positive PF compared to culture-negative PF. Furthermore, there were no cases of infection related to PF regardless of whether culture-positive PF was treated or untreated. The incidence of subsequent C. difficile infection and multidrug-resistant organisms was similar. Discussion: This study suggests antimicrobial treatment for culture positive PF may not be necessary with pathogens that are common contaminants and of low virulence. Interventional studies are needed to validate this strategy.